(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article guarantees the rights, freedoms and legal interests of citizens in the field of education; equality in education, including the creation of conditions for persons with special psychophysical characteristics in their development, in accordance with their health and cognitive abilities, at all levels of basic education and additional education.